Novel turn-on fluorescent biosensors for selective detection of cellular Fe3+ in lysosomes: Thiophene as a selectivity-tuning handle for Fe3+ sensors. (October 2019) - Lim, Bumhee; Baek, Byungyeob; Jang, Kyungkuk; Lee, Na Keum; Lee, Ji Hye; Lee, Yeongcheol; Kim, Jinwoo; Kang, San Won; Park, Jaehyun; Kim, Suzi; Kang, Nae-Won; Hong, Suckchang; et al.
Abstract: Iron-selective turn-on sensors are indispensable tools for understanding iron-related cell death processes and human diseases. In this study, we report a novel class of fluorescent sensors derived from an indolizino[3, 2- c ]quinoline scaffold that exhibit high selectivity for Fe 3+ over other biologically abundant cations in cells, including Fe 2+, Al 3+, Zn 2+, and Mn 2+ . IQ18 works as a ratiometric sensor with a K d value of 7.1 × 10 −7 M and a detection limit of 5.2 nM in ethanol, whereas IQ44 displays fluorescence enhancement upon binding with Fe 3+ in both ethanol and water. In aqueous solution, IQ44 exists as 150-nm nanoparticles. The suppressed fluorescent emission of IQ44 nanoparticles in water is switched on in response to Fe 3+, working as a turn-on nanoparticle sensor. Structure-property relationship analysis with IQ derivatives revealed that the thiophene ring confers selectivity for Fe 3+ . By installing thiophene in IQ44 as a selectivity-tuning handle, fluorescence in the presence of Fe 3+ resulting from restriction of intramolecular rotation (RIR) and increased torsion angle induced by iron demonstrated that IQ44 is specifically localized in lysosomes, where it recognizes cellular Fe 3+ in live cells, as determined using confocal microscopy. In addition, the increased fluorescent puncta of IQ44 in the presence of Fe 3+ colocalized well with the RFP-tagged LC3 proteins (pmRFP-LC3), enabling the detection of the autophagy process. Highlights: We developed novel indolizino[3, 2- c ]quinoline (IQ)-based fluorescent sensors (IQ18 and IQ44 ) for Fe 3+ . IQ18 works as a ratiometric sensor, whereas IQ44 works as a ∼150 nm turn-on nanoparticle sensor for Fe 3+ in water. IQ44 is specifically localized in lysosomes, where it recognizes cellular Fe 3+ in live cells.